JUMPA Vol.3 No.3 Okt 2016 PENGARUH LINGKUNGAN KERJA DAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA GURU HONORER SMK NEGERI DI KOTA BEKASI: PENGARUH LINGKUNGAN KERJA DAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA GURU HONORER SMK NEGERI DI KOTA BEKASI - Rizki Amalia Rosowulan STKIP Kusuma Negara Jakarta (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
The objective of the research is to know the effect of work environment and locus of control on job satisfaction of honorary teacher in public vocational secondary school in the city of bekasi.The methodologhy of this research used the survey method with path analysis applied in testing hypothesis. Respondents were chosen by simple random sampling technique. The conclusions of this research are: (1) there is the positive direct effect of work environment on job satisfaction, (2) there is positive direct effect of locus of control on job satisfaction, and (3) there is positive direct effect of work environment on locus of control.